Foreign Experience of Import Substitution Policy - V. A. Baynov (Мир новой экономики, 2018)
In the current international environment — with fashion on international sanctions, in particular, limiting the possibilities of purchasing high-tech equipment from abroad and dependency of the exchange rate of the ruble against various political provocations — the Russian Federation has faced with the necessity of re-industrialization of the ‘raw’ model of the economy and stimulation of the development of its inner potential. It should be noted that, in accordance with the Plan for promoting import substitution in industry No. 1936-r of 30 September 2014, approved by the order of the Government of the Russian Federation, the Ministry of industry and trade of the Russian Federation has developed and is implementing 22 sectoral plans for import substitution in selected industries of the Russian Federation. In this regard, it is particularly important to study international experience in the field of import substitution policy. The validity and reliability of presented study are achieved by applying a systematic approach and scientific methods of analysis and synthesis, deduction and induction, as well as regulatory, empirical method, etc. As a result of the analysis of international experience, it was possible to identify measures that can improve the efficiency of the state policy of import substitution, including through the use of offset mechanisms in civilian industries and the development of the institution of public procurement, certification, and standardization. In conclusion, the author proposes measures that can improve the policy of import substitution. The practical significance of the article consists in the possibility of applying the results of the study in the elaboration of industrial development programs and further research.